Study on the vertical bearing performance of pile across cave and sensitivity of three parameters - Hui Yun Chen (Nature Portfolio, 2021)
Abstract A new method was used to study the performance of pile across cave. This paper investigated the vertical bearing characteristics of piles cross caves using centrifugal model tests and a theoretical model of sensitivity. Twelve pile scenarios were selected, the first was a conventional pile, 24 cm long and 2.5 cm in diameter, with no karst cave as a control. In the other eleven scenarios the piles passed through karst caves of four different heights, of four different spans, and three different numbers of caves. The results reveal that increasing the height, span, and number of caves all are negative for vertical ultimate bearing capacity of piles. The axial force and unit shaft resistance of piles are great different. According to the ratios of the tip and shaft resistance, caves change the type of piles. The sensitivity of vertical ultimate bearing capacity to these factors from high to low is height, number, and span of caves. Importantly, the bearing characteristics of piles decrease faster once the height of the prototype karst cave is higher than 9 m, but decreases slowly when the cave’s span is greater than 9 m × 9 m.